Investigating factors affecting anemia incidence among adolescent girls in Senior High School, Samarinda - Rahma, Rosyida Muthia; Zuhratunnisa, Aqilah; Nazhirotin, Talitha Syadza; Pawestri, Aulia; Hutapea, Reza Jonathan; Duma, Krispinus; Nugroho, Setyo (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Anemia is a condition of not having enough number of red blood cells or hemoglobin to carry oxygen to supply the body's physiological needs. Anemia can be diagnosed by various ways, the most common and easy to use as an indicator to determine anemia is checking hemoglobin levels. The occurrence of anemia in adolescent girls can be influenced by various factors. Objective : This study aimed to determine the factors that influence the incidence of anemia in adolescent girls at Senior High School in Samarinda city. Research Methods/ Implementation Methods : The design of this research was analytical observational with the cross-sectional approach. Primary data was obtained using the interview with Knowledge, Attitudes, and Practice (KAP) Questionnaire and SAMANTA Questionnaire, and hemoglobin levels were examined using haemometer digital. The sampling technique used was purposive sampling with 98 respondents represented by a 10th grade student in Senior High School 6 Palaran District. The bivariate analysis used was the chi-square test. Results : The results of the analysis between anemia status and the level of knowledge about anemia, nutritional status, menstrual patterns, parental income, and maternal education sequentially obtained showed p-values of 0.645; 0.279; 0.654; 0.551; 0.776 Conclusion/Lesson Learned : Based on the results of the study, it is concluded that there is no significant relationship between the factors and the incidence of anemia in adolescent girls at Senior High School in Samarinda city.